Evaluating pedagogical approaches to enhance students’ comprehension in maritime English: The Norwegian case - Viktoriia Koilo; Maksym Zaitsev (Knowledge & Performance Management, 2024)
This study aims to test and evaluate various pedagogical strategies that can improve students’ comprehension of Maritime English course materials and help them confidently participate in English-based assessments. A comparative research methodology was employed, focusing on integrating specific strategies and tools into the curricula of maritime programs. The study focused on the Norwegian case at NTNU in Ålesund, featuring a 3-year Shipping Management program (Bachelor’s degree) with 45-60 students. The findings from the Norwegian case demonstrate a significant improvement in students’ willingness and ability to engage in English-language assessments, highlighting the effectiveness of the pedagogical approaches implemented. The study results align with existing literature, highlighting the need for continuous innovation in pedagogical approaches to Maritime English education. By the end of the course, 72.2% of students felt comfortable taking the exam in English, compared to only 25.8% at the beginning of the semester. Weekly lectures in English with presentations were identified as the most helpful tool, followed by group work, homework, and vocabulary lists. The use of digital interaction and software tools received a high score – 8.0 out of 10.0. The significant improvement in students’ confidence in English, along with their strong overall ratings of teaching tools, demonstrates the effectiveness of these methods in overcoming initial language barriers. Further recommendations include combining traditional teaching methods with modern digital tools to enhance learning outcomes. By focusing on student-centered approaches and integrating both traditional techniques and technological tools, institutions can foster the development of a more proficient maritime workforce.